A New Methodology to Support Smartness at the District Level of Metropolitan Areas in Emerging Economies: The Case of Santiago de Chile - Palominos-Belmar, P (Elsevier Ltd, 2021)
According to a forecast by the United Nations, by 2030 one in every three people in the world will live in cities with at least half a million inhabitants. Therefore, enabling smarter and resilient cities is one of the key goals to tackling world challenges and ensuring the citizen s wellbeing in the years to come. Various frameworks of indicators have been proposed to evaluate urban smartness with an aim to improve policymakers actions. Nevertheless, recent research shows that despite efforts and initiatives, urban policy actions have yet to achieve the expected results, as smartness is evaluated in an aggregated way, while metropolitan areas are very heterogeneous systems. In this paper, the authors propose a methodological approach to evaluate smartness while considering a city not as a homogeneous space, but as a space divided into different districts with different characteristics and dynamics, and therefore different topologies and citizen needs. This methodology is based on Data Envelopment Analysis (DEA), which sets out to measure the performance of decision-making units (districts) by considering the efficiency of each district, measured by the ratio between its allocated resources (input) and the corresponding smartness score (output). Accordingly, the methodology is highly applicable to cities located in emerging countries, which are characterised by a high disparity of human conditions if we compare them district by district. The approach is illustrated in a case study of the smartness of the metropolitan districts of Santiago de Chile. © 2021 Elsevier Ltd